2020
DOI: 10.3390/ma13183974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Degradation Medium on Water Uptake, Morphology, and Chemical Structure of Poly(Lactic Acid)-Sisal Bio-Composites

Abstract: A series of poly(lactic acid) (PLA) and poly(lactic acid)-based bio-composites (sisal PLA) were prepared and studied by spectroscopic and microscopic techniques as such and after immersion at room temperature in different degradation mediums (i.e., distilled and natural sea water and solutions at pH = 2, 6, and 8). In these conditions, some of their macroscopic and microscopic properties were monitored during a period of 30 days. Water absorption increased with the increasing fiber content regardless of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…Poly(lactic acid) is one of the most readily degradable thermoplastic materials. The factors influencing on the mechanism and speed of PLA degradation under various environmental conditions were analyzed by many authors [8][9][10][11][12][13][14][15]. The main mechanism of PLA degradation is hydrolytic degradation or enzymatic degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(lactic acid) is one of the most readily degradable thermoplastic materials. The factors influencing on the mechanism and speed of PLA degradation under various environmental conditions were analyzed by many authors [8][9][10][11][12][13][14][15]. The main mechanism of PLA degradation is hydrolytic degradation or enzymatic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The most important factor influencing on PLA degradation carried out under natural and laboratory conditions are: the amount of D-lactide isomer in chain structure [13] and the degree of PLA crystallinity [14]. The rate of PLA hydrolysis is also strongly affected by the degradation conditions such as: temperature, humidity, and pH [9,11,15]. Moliner et al [11] reported for PLA samples after immersion during 30 days at room temperature in various aqueous solutions at different pH the limited hydrolysis of the ester bonds in PLA and the formation of few free alcoholic and carboxylic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 presents all characteristics absorption peaks of neat PLA, PLA10 and PLA20. IR reveals the presence of characteristic band absorptions: (i): 2996-2884 cm −1 , the asymmetric and symmetric stretching vibrations of CH 3 , (ii): 1747 cm −1 , an important characteristic band comes from the C O stretching, [10,35] (iii): 1475-1360 cm −1 , these other bends approximately come from the CH 3 and CH bending, (iv): 1270 cm −1 relative to the COC stretching vibration, (v): 1186-1031 cm −1 , the bands of the C O stretching of the CH(CH 3 ) OH end group of PLA [36,37] and (vi): 870-759 cm −1 , the C C stretching vibration and the C COO stretching band, respectively. [38] According to Figure 3, the incorporation of sisal fibers into PLA matrix produces some modifications in spectral regions.…”
Section: Ftir Spectra Analysismentioning
confidence: 99%
“…[8,9] Additional researches on PLA considered its use for applications in textiles, adhesive, agriculture products and packaging [5] due to its thermoplastic processing capacity and biodegradability properties under particular conditions. [10] However, its fragile character persists as it demonstrates a poor rigidity and low elongation at break, and its degradation rate remains slow. [1,2] Research has been carried out to resolve these defects by copolymerizing with other monomers, biocompatible plasticizers or nucleating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in various industries, such as packaging, automotive, construction, pharmaceutical, biotechnology, or horticulture, there is a growing demand for natural fibers. The rapid growing researches of biocomposites and their growing importance in the industry are reflected by the volume of publications or patents during the recent years [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%